The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/aor.14232
|View full text |Cite
|
Sign up to set email alerts
|

Advances in microfabrication technologies in tissue engineering and regenerative medicine

Abstract: Background Tissue engineering provides various strategies to fabricate an appropriate microenvironment to support the repair and regeneration of lost or damaged tissues. In this matter, several technologies have been implemented to construct close‐to‐native three‐dimensional structures at numerous physiological scales, which are essential to confer the functional characteristics of living tissues. Methods In this article, we review a variety of microfabrication technologies that are currently utilized for seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 292 publications
(629 reference statements)
0
10
0
Order By: Relevance
“…In many biological and chemical fields, microfabrication techniques offer an advantage and an opportunity. One possible fabrication technique is photolithography, in which a substrate is hardened by optical or UV light at specific locations [ 69 ]. In contrast, soft lithography enables microstructuring using elastomeric molds, stamps, and photomasks without using the photolithographic technique [ 69 ].…”
Section: Additive Manufacturing Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In many biological and chemical fields, microfabrication techniques offer an advantage and an opportunity. One possible fabrication technique is photolithography, in which a substrate is hardened by optical or UV light at specific locations [ 69 ]. In contrast, soft lithography enables microstructuring using elastomeric molds, stamps, and photomasks without using the photolithographic technique [ 69 ].…”
Section: Additive Manufacturing Technologiesmentioning
confidence: 99%
“…One possible fabrication technique is photolithography, in which a substrate is hardened by optical or UV light at specific locations [ 69 ]. In contrast, soft lithography enables microstructuring using elastomeric molds, stamps, and photomasks without using the photolithographic technique [ 69 ]. Since 3D printing techniques are already found in many fields of medicine, many biopolymers have been used for various 3D printing techniques that achieve sufficient printing resolution.…”
Section: Additive Manufacturing Technologiesmentioning
confidence: 99%
“…Replica molding is conducted by filling a master mold with curable polymers to generate OOCs and scaffolds with desired features and geometries. 88,89 The micro-features on the silicone master mold are generally patterned through a photolithography process. More sophisticated patterns can be generated by a multi-layer workflow using a series of photomasks.…”
Section: Replica Molding and Soft Lithographymentioning
confidence: 99%
“… 19–23 These micropatterns are generated using nano- or microfabrication technologies, including micro-molding and additive manufacturing. 24,25 Meanwhile, it has been suggested that 20 μm was the optimal size for guiding the alignment of CMs. 14,26–29 One explanation is that this size resembles the average functional intercapillary distance.…”
Section: Introductionmentioning
confidence: 99%